(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Temporomandibular joint disorders (TMD) refer to a group of heterogeneous pain and dysfunction conditions involving the masticatory system, reducing life quality of the sufferers. Aim of study: The aim of the study was to evaluate the effectiveness of arthrocentesis with corticosteroid (betamethasone) injection and with sodium hyaluronate injection in treatment temporomandibular joint disorders, in conjunction with a stabilizing splint, for improving function and reducing pain, for preventing further deterioration of the TMJ dysfunction, to maintain improvements over time, and compare between them. Patients and methods: Fifty –four patients with TMJ disorders with age limit between 18 and 55 years of age, 9 males and 36 females, were enrolled in this study. Patients were randomly divided into two groups, in which one group received arthrocentesis with intra-articular corticosteroid (betamethasone) injection (1 ml), and another group received arthrocentesis with intra-articular sodium hyaluronate injection (1 ml) in superior joint space ,in single puncture. Patients were followed at regular interval of 7th day, one month, 3, 6, 9, 12 months (follow up) after last injection. Results: The mean age of patients was 8.873 ± 34.112 years in Group-A treat by betamethasone and10.973± 33.27 years in Group-A treat by sodium hyaluronate (ranged from 18.2 to 55.0 years).